The hybodontiform sharks (Chondrichthyes: Euselachii) from the Upper Jurassic of Torres Vedras, Portugal - Costa, B. L. P. (2022)
ABSTRACT: In this work, the description and classification of a set of fossil shark tooth specimens, from the upper Kimmeridgian-lower Tithonian (Upper Jurassic) of Torres Vedras, was developed. The material, currently housed in the paleontological collection of Sociedade de História Natural, was collected on the surface of the marine deposits at the top of the Praia Azul Member, Lourinhã Formation, Lusitanian Basin. The attribution of the specimens to Hybodus cf. reticulatus, was based on the presence of the following most striking characteristics: a reticulated, spongy root, perpendicular to the crown; a completely to almost completely straight main cusp; several straight, well-defined, and parallel ridges that run from the base of the crown to about half of the height of the main cusp; and flat, well-defined cutting edges.